Removal of reactive oxygen species induced 3’-blocked ends by XPF-ERCC1 - Fisher, Laura A. (2011)
XPF-ERCC1 is a structure-specific endonuclease that is essential for nucleotide excision repair and DNA interstrand cross-link repair in mammalian cells. The yeast counterpart of XPF-ERCC1, Rad1-Rad10, plays multiple roles in DNA repair. Rad1-Rad10 is implicated to be involved in the repair of oxidative DNA damage. To explore the role(s) of XPF-ERCC1 in the repair of DNA damage induced by reactive oxygen species (ROS), cellular sensitivity of the XPF-deficient Chinese hamster ovary cell-line UV41 to ROS was investigated. The XPF-deficient UV41 showed sensitivity to hydrogen peroxide, bleomycin and paraquat. Furthermore, XPF-ERCC1 showed an ability to remove 3’-blocked ends such as 3’-phosphoglycolate from the 3’-end of DNA in vitro. These data suggest that XPF-ERCC1 plays a role in the repair of ROS-induced DNA damage by trimming 3’-blocked ends. The accumulation of various types of DNA damage, including ROS-induced DNA damage due to defects in multiple XPF-ERCC1-mediated DNA repair pathways, could contribute to the accelerated aging phenotypes observed in an XPF-ERCC1 deficient patient.